Discovery of Novel Inhibitors of Cruzain Cysteine Protease of Trypanosoma cruzi - Prates, João Lucas Bruno [UNESP]; Lopes, Juliana Romano [UNESP]; Chin, Chung Man [UNESP]; Ferreira, Elizabeth Igne; Dos Santos, Jean Leandro [UNESP]; Scarim, Cauê Benito [UNESP] (Bentham Science Publishers, 2024)
Chagas disease (CD) is a parasitic disease endemic in several developing countries. According to the World Health Organization, approximately 6-8 million people worldwide are inflicted by CD. The scarcity of new drugs, mainly for the chronic phase, is the main reason for treatment limitation in CD. Therefore, there is an urgent need to discover new targets for which new therapeutical agents could be developed. Cruzain cysteine protease (CCP) is a promising alternative because this enzyme exhibits pleiotropic effects by acting as a virulence factor, modulating host immune cells, and interacting with host cells. This systematic review was conducted to discover new compounds that act as cruzain inhibitors, and their effects in vitro were studied through enzymatic assays and molecular docking. Additionally, the advances and perspectives of these inhibitors are discussed. These findings are expected to contribute to medicinal chemistry in view of the design of new, safe, and efficacious inhibitors against Trypanosoma cruzi CCP detected in the last decade (2013-2022) to provide scaffolds for further optimization, aiming toward the discovery of new drugs.
Keywords: Chagas disease; cruzain; Cysteine proteases; drug development; new compounds; T. cruzi